CA19.9 decrease >15% is a predictor of favourable outcome in patients treated for advanced pancreatic carcinoma: analysis of two independent cohorts. Issue 5 (May 2019) - Laurent, Lucie; Sefrioui, David; Bignon, Anne-Laure; Parzy, Aurélie; Sidali, Sabrina; Hassine, Mélanie; Gangloff, Alice; Galais, Marie-Pierre; Bouhier-Leporrier, Karine; Michel, Pierre; Di Fiore, Frédéric
Abstract: Background: Although carbohydrate antigen 19.9 (CA19.9) is widely used in pancreatic adenocarcinoma (PA), no consensual cut-off value of CA19.9 decrease has been established for treatment monitoring. Methods: This was a retrospective study including patients with a baseline CA19.9 ≥ 37 UI/ml and with locally advanced or metastatic PA from two French centers. CA19.9 measurements were performed at baseline and first CT-scan evaluation. The aim was to use a training set to determine the best cut-off of CA19.9 decrease for predicting progressive disease (PD) and to analyze its performance in an independent validation cohort. Results: A total of 95 and 93 patients were included in the training and validation sets, respectively. A ≤15% CA19.9 decrease was the best cut-off for predicting PD with a sensitivity (Se) = 68% and a specificity (Sp) = 90%. In the validation set, this threshold was associated with Se = 76% and Sp = 83%. A >15% CA19.9 decrease was significantly associated with improved PFS (median 8.3 versus 3.1 months, p < 0.0001) and OS (median 14 versus 7.2 months, p < 0.0001). A >15% CA19.9 decrease was also identified as a factor independently associated with OS (HRa = 0.25, 95% CI:0.14–0.44). Conclusions: A CA 19.9 decrease >15% is a favourable predictor of outcome in patients treated for advanced PA.